INSM1 Is More Sensitive and Interpretable than Conventional Immunohistochemical Stains Used to Diagnose Merkel Cell Carcinoma. (November 2018) - Lilo, Mohammed T.; Chen, Youdinghuan; LeBlanc, Robert E.
Abstract : Merkel cell carcinoma (MCC) is an extremely aggressive skin cancer that must be distinguished from other basaloid cutaneous neoplasms that have different treatments and prognoses. This is sometimes challenging in small shave specimens, crushed samples, lymph nodes, and core needle biopsies. Insulinoma-associated protein 1 (INSM1) immunohistochemistry is a sensitive nuclear marker of neuroendocrine differentiation. INSM1 staining was performed on 56 MCC (47 primary tumors, 9 nodal metastases), 50 skin control cases that included basal cell carcinomas, basaloid squamous cell carcinomas, Bowen disease, sebaceous neoplasms, melanoma, and B-cell lymphomas, and 28 lymph node control cases that included metastatic neuroendocrine neoplasms, melanomas, squamous cell carcinomas, lymphomas, and adenocarcinomas. Percent of staining nuclei (0, <25%, 25% to 50%, 50% to 75%, >75%) and intensity (weak, moderate, strong) were recorded for each sample. All 56 MCC expressed INSM1. By comparison, synaptophysin, CK20, and chromogranin were expressed in 96%, 92%, and 32% of MCC, respectively. While the 3 conventional markers showed significant variability in staining intensity and distribution, INSM1 stained >75% tumor nuclei in 89% of MCC and 50% to 75% of tumor nuclei in 11%. Staining intensity was strong in 85% and moderate in 15%. None of the 50 cutaneous basaloid non-MCC neoplasms in the control group stained with INSM1, and among the lymph node controls 5 of 5 neuroendocrine neoplasms expressed INSM1, confirming that INSM1 staining cannot distinguish MCC from metastatic extracutaneous neuroendocrine carcinoma. INSM1 holds promise as a neuroendocrine marker that can distinguish MCC from its mimickers in the skin and improve detection of sentinel lymph node metastases. Abstract : Supplemental Digital Content is available in the text.